New strategies in the treatment of dyslipidemia: do we know how? - Vrablík, Michal; Ceska, Richard (Seminars in vascular medicine, 2004)
The treatment of dyslipidemia is beyond doubt one of the cornerstones of cardiovascular prevention. If we want to touch and comment on at least the principal news in this broad field, we must simplify and pay attention to only a few selected areas. The focus of this article is on hypercholesterolemia and the treatment options for elevated low-density lipoprotein (LDL)-cholesterol; it also addresses the questions of low high-density lipoprotein (HDL)-cholesterol levels and the treatment of dyslipidemia of the metabolic syndrome. In particular, statins have had accumulation of new evidence resulting in novel indications and new target groups. Modern, even more potent drugs lowering total and LDL-cholesterol levels are available (new statins, e.g., rosuvastatin, pitavastatin, cholesterol absorption inhibitor ezetimibe) More and more attention of the medical public is being paid to dyslipidemia of the metabolic syndrome (so-called lipid triad), which seems to be the greatest rival of LDL-cholesterol among lipid risk factors for cardiovascular disease. In the treatment of this dyslipidemia especially the nuclear peroxisome proliferator-activated receptor (PPAR) agonists play an important role. In particular fibrates but also glithasones are noteworthy in this respect. There are fewer data for fibrates than for statins, but nevertheless evidence documenting benefit of this therapy is growing. A statin and fibrate combination is a promising future approach not only to the treatment of metabolic syndrome. Moreover, niacin, particularly in combination with a statin, might experience a renaissance. HDL-cholesterol level modification attracts more and more discussions; on the horizon there are new therapies of low HDL, for example, cholesterol-ester transfer protein inhibitors, which have been shown to have a potency for increasing HDL by more than 50%.
Keywords: lidé; Clinical Trials as Topic; Hyperlipidemias; hypolipidemika; klinické zkoušky jako téma; hyperlipidemie; Humans; Hypolipidemic Agents